Development of the "SINEMA STARTUP" application for an ecosystem of startup idea creators using the SDLC and Lean Startup methods - Budilaksono, Sularso; Febrianty, Febrianty; Nurzaman, Fahrul; Rosadi, Ahmad; Suwarno, Muhammad Anno; Harkandi Kencana, Woro; Suwartane, I Gede Agus (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Indonesia is a country with a dense population and among them are young people who have the potential to open new jobs. Many university graduates cannot be absorbed by the industry and they have to develop new businesses. The Central Statistics Agency (BPS) reported that the number of unemployed for the August 2020 period increased by 2.67 million people. The number of startups is growing and growing in Indonesia, but the main problems for startups are in the capital, human resources, customers, laws and regulations, and market segments. This research aims to develop the "Sinema Startup" application which aims to create and develop new startups in the right ecosystem. The research methodology uses a combination of SDLC (System Development Life Cycle) and Lean Startup methods with an Object Oriented approach. Respondents are potential startup creators, mentors, developers, testers, incubators, and investors. 1. Based on the results of User Acceptance Testing for the “Sinema Startup” Application, it was found that 93% of creators had no difficulty using the application and the remaining 7% had little difficulty. For mentors, 97% had no difficulty using the application and the remaining 3% had little difficulty. The limitations of this study are that not all stages of seeding, incubation, stocking, and publication can be carried out and the results monitored. The uniqueness of this research involves many users for testing, namely prospective startup creators, mentors, developers, testers, incubators, investors, students, and students. Testing this application requires a testing process that goes along with the growth of the Sinema Startup application.